Exploring the Antecedent of Business Model Innovation in Creating a Sustainable Business - Herdi Qoharrudin; Lily Sudhartio (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This paper aims to study the relationship between business model innovation, contextual ambidexterity, entrepreneurial orientation, and knowledge absorptive capacity on a hotel's performance. In the last few years, there was increasing research interest in business model innovation (BMI), but the conclusions regarding what and how it works and factors that are affecting BMI still require more research. Ambidexterity and entrepreneurial orientation were mentioned frequently and had some positive effects on performance organization. But there have not been many subjects to do with BMI. The capacity to absorb knowledge is also often disclosed as a prerequisite capability for an organization to conduct innovation. The hotel becomes the context that is pulled to test the factors to innovation business model especially with the uncertainty of the pandemic covid affecting hotel business.